Landscape level variation in tick abundance relative to seasonal migration in red deer. - Lars Qviller; Nina Risnes-Olsen; Kim Magnus Bærum; Erling L Meisingset; Leif Egil Loe; Bjørnar Ytrehus; Hildegunn Viljugrein; Atle Mysterud (PLoS ONE, 2013)
Partial migration is common among northern ungulates, typically involving an altitudinal movement for seasonally migratory individuals. The main driving force behind migration is the benefit of an extended period of access to newly emerged, high quality forage along the green up gradient with increasing altitude; termed the forage maturation hypothesis. Any other limiting factor spatially correlated with this gradient may provide extra benefits or costs to migration, without necessarily being the cause of it. A common ectoparasite on cervids in Europe is the sheep tick (Ixodes ricinus), but it has not been tested whether migration may lead to the spatial separation from these parasites and thus potentially provide an additional benefit to migration. Further, if there is questing of ticks in winter ranges in May before spring migration, deer migration may also play a role for the distribution of ticks. We quantified the abundance of questing sheep tick within winter and summer home ranges of migratory (n=42) and resident red deer (Cervus elaphus) individuals (n=32) in two populations in May and August 2009-2012. Consistent with predictions, there was markedly lower abundance of questing ticks in the summer areas of migrating red deer (0.6/20 m(2)), both when compared to the annual home range of resident deer (4.9/20 m(2)) and the winter home ranges of migrants (5.8/20 m(2)). The reduced abundances within summer home ranges of migrants were explained by lower abundance of ticks with increasing altitude and distance from the coast. The lower abundance of ticks in summer home ranges of migratory deer does not imply that ticks are the main driver of migration (being most likely the benefits expected from forage maturation), but it suggests that ticks may add to the value of migration in some ecosystems and that it may act to spread ticks long distances in the landscape.